Letter from Gustav Jacoby to Max Bredig, January 25, 1941 - Jacoby, Gustav (1941)
Gustav Jacoby, a New York immigration lawyer, informs Max Bredig (1902-1977) that he has received Bredig's latest payment for his services.
Keywords: Bredig, Max Albert, 1902-1977; Jacoby, Gustav